2013
DOI: 10.1016/j.eurpsy.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between transcranial direct current stimulation (tDCS) and pharmacological interventions in the Major Depressive Episode: Findings from a naturalistic study

Abstract: tDCS over the DLPFC acutely improved depressive symptoms. Besides the inherent limitations of our naturalistic design, our results suggest that tDCS effects might vary according to prior pharmacological treatment, notably benzodiazepines and some antidepressant classes. This issue should be further explored in controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
2
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 39 publications
5
92
2
8
Order By: Relevance
“…In this method, only significant (according to the p cutoff) predictors in the simple regression analysis are included in the multiple regression analyses. We used similar methodology in a previous study (Brunoni et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this method, only significant (according to the p cutoff) predictors in the simple regression analysis are included in the multiple regression analyses. We used similar methodology in a previous study (Brunoni et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
“…either based on Selective Serotonin Reuptake Inhibitors (SSRI) or Selective Noradrenalin Reuptake Inhibitors (SNRI). Benzodiazepine drugs were tolerated but tapered to a maximum of 20mg/d diazepam (or equivalent) according to previous findings suggesting that benzodiazepines could interfere in tDCS antidepressant mechanisms (Brunoni et al, 2013a;Brunoni et al, 2013c).…”
Section: Subjectsmentioning
confidence: 99%
“…In this open study, which placed the cathode on the right deltoid muscle, there was also a significant reduction in symptoms of about 44%. Finally, in the largest open-label sample to date, Brunoni et al 35 , in 82 patients with unipolar and bipolar depression, found that five days of twice daily tDCS significantly improved depression symptoms. This study also showed that the effects of tDCS are enhanced when associated with antidepressants and decreased with benzodiazepines (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the development of portable, "home-use" tDCS devices could help in this issue, as the number of visits to the clinical center would be dramatically reduced. Moreover, other reviewed studies evaluated the role of tDCS as an augmentation strategy for pharmacotherapy, showing that the combined therapy of tDCS with antidepressant drugs was associated with superior improvement and, interestingly, that tDCS combined with benzodiazepine drugs presented decreased efficacy 35,43 . These findings might be explained by neurophysiological studies in healthy volunteers that evaluated motor evoked potential changes after taking a pharmacological agent (or placebo).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, treatment with tDCS should be considered not only instead of but also as well as antidepressant drugs. Both treatments combined might theoretically induce increased and faster effects than each treatment alone (Brunoni, Ferrucci et al, 2013;.…”
mentioning
confidence: 99%